2015
DOI: 10.1007/s00429-015-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth and refinement of excitatory synapses in the human auditory cortex

Abstract: We had earlier demonstrated a neurofilament-rich plexus of axons in the presumptive human auditory cortex during fetal development which became adult-like during infancy. To elucidate the origin of these axons, we studied the expression of the vesicular glutamate transporters (VGLUT) 1 and 2 in the human auditory cortex at different stages of development. While VGLUT-1 expression predominates in intrinsic and cortico-cortical synapses, VGLUT-2 expression predominates in thalamocortical synapses. Levels of VGLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…This qualitatively unique variability includes a completely duplicated posterior gyrus that emerges from the circular sulcus immediately behind the anterior HG and runs parallel in an anterolateral direction with the anterior HG. This morphology, which is present in gestation (Pundir et al, 2016), has generated interest because it is more commonly observed among people with right-handedness (Marie et al, 2015), musical training (Benner et al, 2017), dyslexia (Leonard et al, 2001), and schizophrenia (Takahashi et al, 2021). Thus, there are questions about the structural and functional significance of duplicated HG.…”
Section: Introductionmentioning
confidence: 99%
“…This qualitatively unique variability includes a completely duplicated posterior gyrus that emerges from the circular sulcus immediately behind the anterior HG and runs parallel in an anterolateral direction with the anterior HG. This morphology, which is present in gestation (Pundir et al, 2016), has generated interest because it is more commonly observed among people with right-handedness (Marie et al, 2015), musical training (Benner et al, 2017), dyslexia (Leonard et al, 2001), and schizophrenia (Takahashi et al, 2021). Thus, there are questions about the structural and functional significance of duplicated HG.…”
Section: Introductionmentioning
confidence: 99%